IMPLEMENTATION OF CUTI WINS FREE (CMB) FOR NARAPIDANA BASED ON THE LAW OF LAW AND HUMAN RIGHTS NO. M.01.PK.04.10 YEAR 2007 REGARDING TERMS AND PROCEDURES FOR IMPLEMENTATION OF ASIMILATION, LIBERAL EXEMPTION, LEAVE WHICH ARE FREE, AND LEAVES LEARNED (Study - WISNU WAHYUDI, ST. A2021141028, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACTThis thesis discusses the implementation of free leave (CMB) for Prisoners Based on the Law and Human Rights Candidate RI NO. M.01.PK.04.10 Year 2007 About Terms and Procedures for Implementation of Assimilation, Parole, Free Before Leave, and Conditional Leave (Study In Class II A Pontianak). The approach method used in this research is the normative juridical approach. From the results of this thesis research obtained the conclusion that the Implementation of Free Leave Leave (CMB) For Prisoners In Class IIA Penitentiary Pontianak. Based on the Regulation of the Minister of Justice and Human Rights Number M.01.PK.04.10 of 2007 on Terms and Procedures for Implementation of Assimilation, Conditional Clearance, Free Leave Leave, and Conditional Leave in Article 1 paragraph 3 mentioned the definition of Leave-Off is the process of Preparation of Prisoners And Criminal Children outside the Penal Institution after serving at least 2 (nine) months of good crime at least 9 (nine) months of good behavior while in paragraph (2) mentioned Conditional Leave is a process of fostering outside the Penitentiary for Prisoners and Criminal Children Sentenced to 1 (one) year and below, must have at least% (two thirds) of the criminal offense. Constraints faced in the implementation of Free Before Leave (CMB) In Prison Class IIA Pontianak in performing services and the fulfillment of the rights of prisoners, especially in the Implementation of Leave Before Free (CMB) experienced several obstacles / obstacles. This thus makes one of the factors causing the failure of Class IIA Pontianak in conducting guidance on prisoners. The obstacles / barriers can be divided into 2 (two) ie non-juridical barriers and juridical barriers. Efforts That Can Be Done To Overcome The Constraints In The Implementation Of Free Leave Forward (CMB) For Prisoners In Class IIA Penitentiary Pontianak Provide illumination and explanation of Free Before Leave (CMB) to prisoners. The provision of enlightenment to the inmates is very important, because without understanding the intent and purpose of the coaching will certainly result in the prisoner becomes indifferent even against the proposal of Free Leave (CMB). Many inmates feel themselves too disrespectful and assume anything given to them from the officer should be taken for granted without any denial. This accepting attitude results in inmates acting like instruments without creativity so often contrary to their conscience. Therefore it is important to enlighten the inmate about the function and purpose of coaching for him, as well as their position in the institution to provide a picture of the future after leaving the institution later. After the inmate understands the purpose and purpose of coaching for him, it is expected to2encourage him / her to seriously follow and accept the coaching program well, one of which is the provision of Free Leave Leave (CMB). Without a positive will from the conscience's own conscience, coaching will be difficult to achieve to achieve satisfactory results. That is why information on Free Cause (CMB) is held to awaken the conscience's awareness to arise awareness from the mind to participate in reaching the community's goals.Keywords: Implementation, Leave, Go For Free, Prisoners.ABSTRAK Tesis ini membahas pelaksanaan cuti menjelang bebas (CMB) Bagi Narapidana Berdasarkan Permen Hukum Dan HAM RI NO. M.01.PK.04.10 Tahun 2007 Tentang Syarat Dan Tata Cara Pelaksanaan Asimilasi, Pembebasan Bersyarat, Cuti Menjelang Bebas, Dan Cuti Bersyarat (Studi Di Lembaga Pemasyarakatan Kelas II A Pontianak). Metode pendekatan yang digunakan dalam penelitian ini adalah pendekatan yuridis normatif. Dari hasil penelitian tesis ini diperoleh kesimpulan bahwa Pelaksanaan Cuti Menjelang Bebas (CMB) Bagi Narapidana Di Lembaga Pemasyarakatan Kelas IIA Pontianak. Berdasarkan Peraturan Menteri Hukum dan Hak Asasi Manusia Nomor M.01.PK.04.10 Tahun 2007 tentang Syarat dan Tata Cara Pelaksanaan Asimilasi, Pembebasan Bersyarat, Cuti Menjelang Bebas, dan Cuti Bersyarat pada Pasal 1 ayat 3 disebutkan pengertian Cuti Menjelang Bebas adalah proses Pembinaan Narapidana dan Anak Pidana di luar Lembaga Pemasyarakatan setelah menjalani sekurang-kurangnya % (dua per tiga) masa pidananya minimal 9 (sembilan) bulan berkelakuan baik sedangkan di ayat (2) disebutkan Cuti Bersyarat adalah proses Pembinaan di luar Lembaga Pemasyarakatan bagi Narapidana dan Anak Pidana yang dipidana 1 (satu) tahun ke bawah, sekurang-kurangnya telah menjalani % (dua per tiga) masa pidana. Kendala-kendala yang dihadapi dalam pelaksanaan Cuti Menjelang Bebas (CMB) Di Lembaga Pemasyarakatan Klas IIA Pontianak dalam melakukan pelayanan dan pemenuhan terhadap hak Narapidana khususnya dalam Pelaksanaan Cuti Menjelang Bebas (CMB) mengalami beberapa kendala/hambatan. Hal demikian menjadikan salah satu faktor penyebab kegagalan LAPAS Klas IIA Pontianak dalam melakukan pembinaan terhadap Narapidana. Adapun kendala/hambatan dapat dibagi 2 (dua) yakni hambatan yang bersifat non-yuridis dan hambatan yang bersifat yuridis.Upaya-Upaya Yang Dapat Dilakukan Untuk Mengatasi Kendala-Kendala Dalam Pelaksanaan Cuti Menjelang Bebas (CMB) Bagi Narapidana Di Lembaga Pemasyarakatan Kelas IIA Pontianak Memberikan penerangan dan penjelasan mengenai Cuti Menjelang Bebas (CMB) kepada narapidana. Pemberian penerangan kepada narapidana sangatlah penting, karena tanpa memahami maksud dan tujuan pembinaan tersebut tentu akan berakibat narapidana menjadi acuh tak acuh bahkan menentang adanya pengusulan Cuti Menjelang Bebas (CMB). Banyak narapidana yang merasa dirinya terlalu hina dan beranggapan apapun yang diberikan pada dirinya dari petugas harus diterima begitu saja tanpa ada suatu bantahan. Sikap menerima semacam ini mengakibatkan narapidana akan bertindak seperti alat tanpa adanya kreatifitas sehingga sering bertentangan dengan hati nuraninya. Karenanya sangatlah penting diadakan penerangan kepada narapidana tentang fungsi dan tujuan pembinaan baginya, serta kedudukan mereka dalam lembaga untuk memberikan gambaran3masa depan setelah keluar dari lembaga nantinya. Setelah narapidana tersebut mengerti maksud dan tujuan pembinaan baginya, diharapkan akan mendorong dirinya untuk bersungguh-sungguh mengikuti dan menerima program pembinaan dengan baik, yang salah satunya adalah pemberian Cuti Menjelang Bebas (CMB). Tanpa adanya kemauan yang positif dari hati nurani narapidana itu sendiri maka pembinaan akan sulit dilaksanakan untuk mencapai hasil yang memuaskan. Karena itulah diadakan penerangan mengenai Cuti Menjelang Bebas (CMB) untuk menggugah kesadaran para narapidana agar timbul kesadaran dari batinnya untuk ikut berpartisipasi mencapai tujuan masyarakat. Kata Kunci: Pelaksanaan, Cuti ,Menjelang Bebas, Narapidana.